a EVALUASI APLIKASI QUIZIZZ DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Siti Kholidatur Rodiyah; Sakia Amanda Deviana Putri; Roudlotul Jannah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2024)
The point of this exploration is to find out how to create an innovative design using the quizizz application, implementation and obstacles found in implementing the use of the quizizz application. This research is quantitative research. Information gathering methods include perception, meetings, and recording. Research strategies use information gathering methods, information displays, and objectives. This test shows that the most common way of evaluating Islamic Cultural History learning training using the quizizz application is through three stages, namely creating pointers, planning an iterative inquiry network, and entering questions created in the quizizz application. The implementation of the evaluation within the framework of the quizizz application went through three stages, namely at the launch of the movement starting with conveying good news and prayers, in the middle action assessing learning using the quizizz application, then at the end closing with reflection. and petitions. There are four factors that hinder evaluation based on quiz applications, namely: raising doubts according to markers and networking which takes almost the whole day, there are still many instructors who cannot use quiz applications, students often neglect to bring cell phones, there is still no supporting organization, let alone a web network who frequently experience disruption.